Administration of hepatitis B vaccine in winter as a significant predictor of the poor effectiveness of vaccination in rural Mongolia: evidence from a nationwide survey - Davaalkham, Dambadarjaa (BMJ Group, 2007)
BACKGROUND: Universal hepatitis B (HB) immunisation is the most effective means for prevention of hepatitis B virus (HBV) infection worldwide. Maintaining the vaccine cold chain is an essential part of a successful immunisation programme. Our recent nationwide survey in Mongolia has observed significant urban–rural differences in the prevalence of HBV infection among vaccinated cohorts. OBJECTIVE: To examine whether the administration of HB vaccine in winter contributes to these residential discrepancies on the effectiveness of vaccination. DESIGN AND SETTING: In 2004, a nationwide serosurvey was carried out covering both urban and rural areas of Mongolia. Sampling was multistage, with random probability from all public schools in the country. PARTICIPANTS: A random sample of 1145 children (51.7% boys; aged 7–12 years), representative of Mongolian elementary school children. RESULTS: Multivariate logistic regression analysis identified that total (past and current) HBV infection (OR 2.31, 95% CI 1.20 to 4.42; p = 0.012) was independently associated with the administration of all HB vaccines in winter. An increased OR for current HBV infection was also observed (OR 2.58, 95% CI 0.87 to 7.68; p = 0.089), but without significance. Interestingly, after stratifying by residence, the association between winter vaccination and total HBV infection was evident for rural (p = 0.008) but not for urban areas (p = 0.294). The frequency of vaccine‐induced immunity was significantly (p = 0.007) lower for those who received HB vaccine at birth during winter in rural areas. CONCLUSION: Administration of HB vaccine during winter is an important predictor of the low effectiveness of vaccination in rural Mongolia. To improve the effectiveness of HB vaccination in remote areas, cold chain control should be addressed with particular attention to the winter season.